(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study analyzes the correlation between QoR-40 questionnaire value and the Pupillary Pain Index as an assessment for the quality of recovery of postoperative patients receiving multimodal analgesia (Paracetamol + NSAID + PCA Opioid) in Dr. Soetomo Hospital. An observational analytic study with cross-sectional design was conducted on patients aged 18-60 years who underwent elective surgery with general anesthesia at Dr. Soetomo Hospital Surabaya and receiving multimodal analgesia therapy, which includes intravenous paracetamol 4 x 500 mg, intravenous ketorolac 3 x 10 mg, and intravenous fentanyl via PCA. Recovery quality checks were performed at 12 and 24 hours postoperatively. Retrieval of data in the form of a QoR-40 questionnaire and pupillary pain index examination using algiscan® pupillometry. Both parameters will be analyzed by correlation test. The total need for fentanyl and PCA demand dose was also evaluated for use within 24 hours postoperatively. From 46 samples, obtained characteristics of studyare widely distributed in terms of age, sex, anthropometry, and preoperative physical status. The average total fentanyl PCA requirement is relatively small at 0.28 mcg / kg / hour. The correlation formed between QoR- 40 and pupillary pain index is significant. It can be concluded that Pupillary Pain Index can replace the QoR-40 questionnaire as an alternative assessment of the quality of recovery of patients after surgery